The Impact Of The Vietnam Drip Method On The Quality Of Robusta Coffee Drinks In Pasaman Barat - Muhammad, Said Fajar; Asnur, Lise (Universitas Negeri Padang, 2025)
This study aims to identify the effect of the Vietnam Drip brewing method on the quality of taste, aroma, and texture of Robusta coffee, and to analyze the relationship between these variables. This type of research is quantitative research with experimental methods using primary data. Instrument trials include normality tests, homogeneity tests, t-tests, and correlation tests. The results show that the Vietnam Drip method produces coffee brews with varying taste, aroma, and texture characteristics depending on the level of coffee bean grind (fine, medium, and coarse). Based on the results of the t-test, the level of grind fineness does not significantly affect taste and aroma (p>0.05), but significantly affects texture (p=0.027). The correlation test shows a fairly strong relationship between aroma and texture (r=0.696), while taste does not show a significant relationship with either variable. Thus, it can be concluded that the size of the coffee bean grind plays an important role in determining the texture of Robusta coffee brewed with the Vietnam Drip method. Therefore, for baristas and coffee enthusiasts, choosing the right grind is crucial for achieving the desired texture without sacrificing taste and aroma.